MgAlSiCrFeNi low-density high entropy alloy processed by mechanical alloying and spark plasma sintering: Effect on phase evolution and thermal stability - Singh N.; Shadangi Y.; Shivam V.; Mukhopadhyay N.K. (My University, 2025)
Equiatomic MgAlSiCrFeNi low-density high-entropy alloy (LDHEA) was prepared by mechanical alloying followed by spark plasma sintering (SPS). The phase evolution, chemical composition, and thermal stability of the alloy were analyzed by X-Ray diffraction (XRD), transmission electron microscopy (TEM), scanning electron microscopy (SEM), and differential scanning calorimetry (DSC) techniques. Formation of a BCC phase having a lattice parameter of 0.2876±0.03 nm and undissolved Si (~3 at%) was observed after milling of 60 h. DSC experiment up to 1200 °C (1473 K) shows five exothermic heating events corresponding to various phase transformations, which were matched with the results obtained from XRD experiments. It has been found that the alloy after high temperature annealing led to the evolution of a major B2 phase (a=0.289 nm) and also BCC phase along with small amounts of FCC Al-Mg solid solution phase, FCC 1 (a= 0.4082 nm) and FCC 2 (a= 0.4215 nm), monoclinic Al13Fe4 (a= 1.549 nm, b= 0.808 nm, c= 1.248 nm, α = β = 90˚), Mg2Si (a= 0.6351 nm), Cr5Si3 (a=b= 0.9165 nm, c= 0.4638 nm). The spark plasma sintered (SPS) sample also exhibited BCC and B2 phases coexisting with minor amounts of other phases observed for 800 °C (1073 K) annealed sample. The co-exsistence of minor phases with parent BCC phase in SPSed alloy (having relative density of ~99.40%) has led to significantly high hardness and modulus of elasticity of ~9.98 ± 0.3 GPa and 229 ± 0.3 GPa respectively. Various thermodynamics parameters were calculated in order to correlate with the experimental findings of phase evolution and stability of the annealed powder and spark plasma sintered alloy. © 2021 Elsevier B.V.